2018
DOI: 10.3892/etm.2018.5942
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-27a participates in the pathological process of depression in rats by regulating VEGFA

Abstract: The present study aimed to determine the expression of vascular endothelial growth factor A (VEGFA) and microRNA (miRNA/miR)-27a in hippocampal tissues, and serum from a depression model of rats. In addition, the present study aimed to understand the mechanism of regulation of miR-27a in depression. A total of 40 male rats were selected, and divided into the control and depression model groups. The rats in the model group were subjected to 14 types of stimulations to model depression. By determining the body w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…16 fed dams. We report that a reduction in miRNA27a in response to Exercise and PregEx matched a reciprocal increase in VEGFA protein expression, an association that was recently validated in rat hippocampal tissue [6]. The role of miRNAs in regulating placental vasculogenesis and angiogenesis are yet to be fully explored.…”
Section: Accepted Manuscriptmentioning
confidence: 67%
See 1 more Smart Citation
“…16 fed dams. We report that a reduction in miRNA27a in response to Exercise and PregEx matched a reciprocal increase in VEGFA protein expression, an association that was recently validated in rat hippocampal tissue [6]. The role of miRNAs in regulating placental vasculogenesis and angiogenesis are yet to be fully explored.…”
Section: Accepted Manuscriptmentioning
confidence: 67%
“…Studies in Plgf -/mice demonstrate the importance of PlGF during placental blood vessel development, where these mice have reduced implantation sites and placental vascular branching as well as increased blood spaces [5]. Recent studies demonstrate that VEGFA expression can be modulated by micro RNAs (miRNA), including miRNA27a [6], which may implicate this miRNA in altered vasculogenesis and/or angiogenesis in complicated pregnancies.…”
Section: Introductionmentioning
confidence: 99%
“…Postmortem brain studies revealed that the miRNA-27a expression was downregulated in the prefrontal cortex of depressed suicide subject [ 41 ]. Depressed rats exhibited decreased levels of miRNA-27a in the hippocampus and peripheral blood [ 42 ]. Honokiol, a bioactive polyphenolic substance, significantly shortened the immobility duration of LPS mice in both TST and FST experiments, which was strongly related to decreased NF-κB activity in the hippocampus [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNA is small nucleic acids consisting of about ~ 20 nucleic acids, which involved in various biological pathways, and recent studies have reported that miRNA plays a key role in neurological diseases. In this study, we found that the expressions of miRNAs were reversed its abnormal changes by DON and SIP3L cotreatment, including miRNA-15a, -27a, 32, which are linked with in ammation or apoptosis pathways [46][47][48][49], indicating that the therapeutic mechanism of SIP3 and DON might underlie miRNA regulation. Further studies are required to unravel the detailed mechanism.…”
Section: Discussionmentioning
confidence: 67%